Bacterial Endophytes from Legumes Native to Arid Environments Are Promising Tools to Improve Mesorhizobium–Chickpea Symbiosis under Salinity - Roukaya Ben Gaied; Imed Sbissi; Mohamed Tarhouni; Clarisse Brígido (Biology, 2024)
Symbiotic nitrogen fixation is a major contributor of N in agricultural ecosystems, but the establishment of legume–rhizobium symbiosis is highly affected by soil salinity. Our interest is focused on the use of non-rhizobial endophytes to assist the symbiosis between chickpea and its microsymbiont under salinity to avoid loss of production and fertility. Our aims were (1) to investigate the impact of salinity on both symbiotic partners; including on early events of the Mesorhizobium-chickpea symbiosis, and (2) to evaluate the potential of four non-rhizobial endophytes isolated from legumes native to arid regions (Phyllobacterium salinisoli, P. ifriqiyense, Xanthomonas translucens, and Cupriavidus respiraculi) to promote chickpea growth and nodulation under salinity. Our results show a significant reduction in chickpea seed germination rate and in the microsymbiont Mesorhizobium ciceri LMS-1 growth under different levels of salinity. The composition of phenolic compounds in chickpea root exudates significantly changed when the plants were subjected to salinity, which in turn affected the nod genes expression in LMS-1. Furthermore, the LMS-1 response to root exudate stimuli was suppressed by the presence of salinity (250 mM NaCl). On the contrary, a significant upregulation of exoY and otsA genes, which are involved in exopolysaccharide and trehalose biosynthesis, respectively, was registered in salt-stressed LMS-1 cells. In addition, chickpea co-inoculation with LMS-1 along with the consortium containing two non-rhizobial bacterial endophytes, P. salinisoli and X. translucens, resulted in significant improvement of the chickpea growth and the symbiotic performance of LMS-1 under salinity. These results indicate that this non-rhizobial endophytic consortium may be an appropriate ecological and safe tool to improve chickpea growth and its adaptation to salt-degraded soils.